Circadian Rhythm, Lifestyle and Health: A Narrative Review - Dariush FARHUD; Zahra ARYAN (Tehran University of Medical Sciences, 2018)
Background: The circadian rhythm regulation plays a crucial role in people`s healthy lives affected by factors consisting of cosmic events related to the universe and earth, environmental factors (light, night and day duration, seasons) and lifestyles. These factors changes lead to disturbance of circadian rhythm and it causes increasing the incidence of mental diseases like depression and physiological problems like cancers, cardiovascular disease and diabetes. Methods: The present review searched Elsevier, SID, Pub Med, Springer, and Google Scholar databases for relevant articles were published between 1996 and 2017. Keywords used included lifestyle, circadian rhythm, cancer, metabolic diseases and cosmic factors. Results: Circadian rhythm can be affected by lifestyle, heredity, cosmos spin and seasonal factors. Two first factors have physically direct effects on circadian rhythm and health, while other factors influence on them mentally. After all, all of them lead to cancer, cardiovascular diseases and metabolic obesity. Conclusion: Although environmental factors are universal events which are unrelated to human control but affect human`s body and circadian rhythm. Other factors are manageable by human to prevent disturbance of circadian rhythm making physical disorders.